2020
DOI: 10.2147/cmar.s250688
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Clinical Prognostic Value of the Neutrophil-to-Lymphocyte Ratio in Brain Metastases from Non–Small Cell Lung Cancer-Harboring EGFR Mutations</p>

Abstract: Purpose Several studies have explored the correlation between the neutrophil-to-lymphocyte ratio (NLR) and the prognosis of patients with lung cancer. However, little is known about the correlation between the pretreatment NLR and the prognosis of patients with brain metastases from non–small cell lung cancer (NSCLC)-harboring mutations in the epidermal growth factor receptor ( EGFR ) gene. We sought to evaluate the predictive values in brain metastasis from lung adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…On univariate analysis of overall survival, elevated preNLR was an independent prognostic poor factor along with KPS < 70, extracerebral metastases, age ≥ 65, without postoperative radiotherapy and targeted therapy. These results have been supported by other studies [ 22 , 26 ]. When the high and low NLR groups are analyzed, it becomes apparent that preNLR is associated with the BM lesions of both supra- and infratentorial and the severe peritumoral edema, thereby causing severe neurological symptoms ( Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On univariate analysis of overall survival, elevated preNLR was an independent prognostic poor factor along with KPS < 70, extracerebral metastases, age ≥ 65, without postoperative radiotherapy and targeted therapy. These results have been supported by other studies [ 22 , 26 ]. When the high and low NLR groups are analyzed, it becomes apparent that preNLR is associated with the BM lesions of both supra- and infratentorial and the severe peritumoral edema, thereby causing severe neurological symptoms ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, previous studies have shown the prognostic value of NLR in other nervous system disorders, including glioblastoma [15] , traumatic brain injury [16] , Meningiomas [17] , Alzheimer's disease [18] and lymphoma [19] . The cutoff value of NLR reported in previous literature is around 2.0–7.0 [ 12 , 14 , [20] , [21] , [22] ]. However, few studies focused on the prognostic value of elevated preNLR in LUAD patients with BM.…”
Section: Introductionmentioning
confidence: 99%
“…A NLR threshold of 3 has been investigated in a number of trials in NSCLC to differentiate high and low risk patients. A recent example of this can be seen in a study which investigated the role of NLR in patients with stage IV disease with brain metastasis and found that pretreatment NLR ≥3 correlated with worsened overall survival 8 . The first data in the stage III NSCLC setting was published by Wang et al who also investigated the baseline prechemoradiotherapy NLR for patients treated with consolidation durvalumab.…”
Section: Discussionmentioning
confidence: 99%
“…NLR is calculated by the absolute neutrophil count divided by the absolute lymphocyte count. Based on previous studies, 8 , 13 we used a threshold ratio of 3 to define high and low NLR. Sustained NLR was defined as NLR ≥ 3 in both pre‐CRT and predurvalumab blood tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation